Komunikasi Bahasa Tubuh dalam Perspektif Al-Qur`an; : Studi Tafsir Al-Qur'ān Al-Aẓĭm dan Jāmi` Li Aḥkām al-Qur`ān - Firdausa, Salsabila; Ania Zulita, Melisa (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
In fact, communication affects every element of life, which makes it extremely vital. The process of conveying messages and gaining many meanings between two individuals is called communication. When it comes to communicating in day-to-day activities, body language accounts for 65% and verbal communication for 35%. In order to promote a sense of fraternity, this study aims to gather and examine passages from the Qur'an about body language communication in people. If we look at the actual facts, communication is one of the basic human needs that is very important. Even before humans could use words to communicate verbally, the process of communication was already taking place. Often, however, obstacles hinder effective communication. Mismatches between verbal and non-verbal messages can result in incomplete information and cause messages to be poorly understood. Therefore, it is important to educate about the importance of using effective body language, especially for communicators who often deliver messages directly. So in this study will be explained related to the importance of body language communication from the perspective of the Qur'an. The research methodology used in this study is qualitative research, which yields desk research with a sample size of ten thousand. The investigators also use the comparative method. The results of this study show that the ability to communicate in body language is present in Q.S. Abasa:1, Q.S. Al-Muṭaffifīn:30, Q.S. Al-Furqān:27, Q.S. Luqman:18–19, and Q.S. Al-Māidah:83. There are several categories of body language communication, such as facial, oral, facial, and oral.